JMJD8 is a positive regulator of TNF-induced NF-κB signaling - Yeo, K.S.; Tan, M.C.; Wong, W.Y.; Loh, S.W.; Lam, Y.L.; Tan, C.L.; Lim, Y.Y.; Ea, C.K. (Nature Publishing Group, 2016)
TNF-induced signaling mediates pleiotropic biological consequences including inflammation, immunity, cell proliferation and apoptosis. Misregulation of TNF signaling has been attributed as a major cause of chronic inflammatory diseases and cancer. Jumonji domain-containing protein 8 (JMJD8) belongs to the JmjC family. However, only part of the family members has been described as hydroxylase enzymes that function as histone demethylases. Here, we report that JMJD8 positively regulates TNF-induced NF-κB signaling. Silencing the expression of JMJD8 using RNA interference (RNAi) greatly suppresses TNF-induced expression of several NF-κB-dependent genes. Furthermore, knockdown of JMJD8 expression reduces RIP ubiquitination, IKK kinase activity, delays IκBα degradation and subsequently blocks nuclear translocation of p65. In addition, JMJD8 deficiency enhances TNF-induced apoptosis. Taken together, these findings indicate that JMJD8 functions as a positive regulator of TNF-induced NF-κB signaling.